Imagens regionais e restaurantes temáticos: comida, cultura e lugar - Lima, Maria de Fátima Farias de (2010)
The study of the dissertation presents has as purpose to understand the pratical discourse and (re)construction of a regional image of food, used by the owner of the two thematic restaurants, located in the region of Fortaleza, Ceará: Chica Sinhá and Lá na Roça. Especialized in sertão’s culinary, this firms shows us, in details of their compositions, a large field of simbolic relactions and productions, from them emerge and which help to build. This way, I back to look for the history, as a process full of cognitive staying and cognitive ruptures, searching to reflect about the way of social objetivation of the regional cusine ideia, adopt and reframe by the mentioned restaurants. Following a verified trend also in the other places of Brasil and the rest of the world, in Ceará, the adoption of tourism by the government (as a growing form of aceleration the local economic devoloping) and the expressions changings imposed to the modern urban food consumption (driven by industrialization and padronization of the gender food) they are in the midle of conceptions and padronization movements this type of peculiar cusine.